Relationship between Mal Presentation, Contractions and Baby Weight with Prolonged Parturition in the Teluk Lubuk Health Center Working Area in 2020 - Indah Sari Dewi; Helni Anggraini; Titin Dewi Sartika Silaban (Institute of Computer Science (IOCS), 2022)
Background: The incidence of prolonged labor is the 3rd cause of maternal mortality in Indonesia. The incidence of prolonged labor in 2007 and 2012 remains the same, namely 5%. Prolonged labor can cause complications for the mother and fetus. Factors that affect prolonged labor include maternal factors, fetal factors, and birth canal factors. Based on a preliminary survey in the Lubuk Bay Health Center Working Area in 2020, there were 435 deliveries where it was known that there were 58 cases of delivery referrals of which 28 cases were due to prolonged labor, 13 cases of post-term pregnancy, 17 cases of Pre-eclampsia and other causes. The purpose of this study was to determine the relationship between mal presentation, contraction and infant weight with the incidence of prolonged labor in the Teluk Lubuk Health Center Work Area in 2020. This type of research was analytic using a cross-sectional design. This research will be conducted in August 2021. The population in this study were all mothers who gave birth in January-December 2020. The sample was taken by purposive sampling technique. This research data uses secondary data. The results of univariate analysis are known to be more than half (51.8%) with an abnormal presentation. more than half of respondents with abnormal contractions (50.4%). more than half (61.3%) the weight of the baby is at risk. more than half (51.8%) of mothers with prolonged labor. From the results of the chi-square test, there is a relationship between malpresentation and prolonged labor, it is obtained that P value = 0.000. there is a relationship between contractions and prolonged labor, the P value = 0.005. the weight of infants with prolonged labor obtained P value = 0.001. So it is recommended to improve the quality of services, especially health services for pregnant women by running an integrated ANC program with quality.